Interpreting Proverbs 11:18-31, Psalm 73, and Ecclesiastes 9:1-12 in light of, and as a response to, Thai Buddhist interpretations : a contribution to Christian-Buddhist dialogue - Haug, Kari Storstein. (Studies in Systematic Theology, 2012)
This book discusses how three Old Testament wisdom texts can be interpreted in light of, and as a response to Thai Buddhist interpretations. Its central aim is to explore a new method in Buddhist-Christian dialogue that has three steps. First, Buddhists are asked to reflect on biblical texts, second, the texts are analyzed by placing Christian and Buddhist perspectives side by side, and finally points of convergence and difference are established in order to provide a platform for further dialogue. The study succeeds in demonstrating that the method explored is a fruitful approach to interreligious dialogue which takes interpretations of biblical texts by the religious 'other' seriously, and manages to both affirm commonalities and face religious difference.